PERBEDAAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN JIGSAW DENGAN TWO STAY TWO STRAY PADA PELAJARAN EKONOMI - Anisa Khoerunnisa; Yoni Hermawan; Gugum Gumilar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The problem in this study is based on the low learning outcomes of students, especially in economics subjects in Class XI SMA Negeri 5 Tasikmalaya. This study aims to improve students' economic learning outcomes by comparing the cooperative learning model type Jigsaw and Two Stay Two Stray. The method used in this study is a quasi-experiment with a comparative type using a pre-test post-test nonequivalent multiple group design. The results show that both models are effective, but the Two Stay Two Stray model is superior with a higher N-Gain score.